2017
DOI: 10.1017/s1352465817000583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Outcomes Between Lesbian, Gay, Bisexual and Heterosexual Individuals Receiving a Primary Care Psychological Intervention

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
3
16
0
2
Order By: Relevance
“…One study (1.6%) was set in a prison for male offenders (Adamson, Gibbs, & McLaughlin, 2015), whilst two papers (3.3%) studied outcomes with veterans (Clarkson et al ., 2016; Giebel, Clarkson, & Challis, 2014). One study explored the effectiveness of an IAPT for deaf patients (Young et al ., 2017), whilst another explored differences in outcomes based on sexual orientation (Rimes et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (1.6%) was set in a prison for male offenders (Adamson, Gibbs, & McLaughlin, 2015), whilst two papers (3.3%) studied outcomes with veterans (Clarkson et al ., 2016; Giebel, Clarkson, & Challis, 2014). One study explored the effectiveness of an IAPT for deaf patients (Young et al ., 2017), whilst another explored differences in outcomes based on sexual orientation (Rimes et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…a Moderator analysis for 'primary condition' was not undertaken for the WSAS outcome measure as all studies included were deemed to be investigating mental health with none focusing purely on physical health; *Significant at p < .05 threshold; **Significant at p < .01 threshold; ***Significant at p < .0001 threshold, between subgroup differences significant at Bonferroni-adjusted p < .01 threshold for multiple testing (in bold). IAPT for deaf patients (Young et al, 2017), whilst another explored differences in outcomes based on sexual orientation (Rimes et al, 2018).…”
Section: Mental Health Conditions and Populationsmentioning
confidence: 99%
“…An example of intervention effectiveness evaluation is a published comparison of Improving Access to Psychological Therapies (IAPT) treatment outcomes (Rimes et al 2018). It found that, compared with heterosexual women, lesbian and bisexual women showed smaller reductions in depression and impairment, controlling for age, ethnicity, employment, baseline symptoms, number of sessions, and intervention type.…”
Section: Intervention Effectiveness In Sexual Minority Populationsmentioning
confidence: 99%
“…Broadly, these papers were thematically divided across three areas. Firstly, six papers focused on professional opinions and treatment outcomes of LGBT+ mental health [70,77,82,87,98,99]. Secondly, 22 papers were concerned with the incidence of mental health problems, and the risk factors associated with the elevated rates of mental health problems within LGBT+ populations [75,76,[78][79][80][81][83][84][85][86][90][91][92][93][94][95][96][97][100][101][102]106].…”
Section: Mental Healthmentioning
confidence: 99%